MO993IMMUNOSUPPRESSION MINIMIZATION IN KIDNEY TRANSPLANT RECIPIENTS HOSPITALIZED FOR COVID-19. (29th May 2021) - Anton Pampols, Paula; Trujillo, Hernando; Melilli, Edoardo; Urban, Blanca; Sandino Pérez, Justo; Favà, Alexandre; Gutierrez, Eduardo; Bestard, Oriol; Mancebo, Esther; Sevillano, Angel; Cruzado, Josep; Morales, Enrique
Abstract: Background and Aims: Immunosuppressed patients such as kidney transplant recipients (KTs) have increased mortality risk in the setting of coronavirus disease 2019 (COVID-19). The role and management of chronic immunosuppressive therapies during COVID-19 must be characterized. Method: Herein, we report the follow-up of a cohort of 47 KTs admitted at two Spanish Kidney Transplant Units who survived COVID-19. The impact of the management of immunosuppression during COVID-19 on graft function and immunologic events was evaluated. Results: At least one immunosuppressive agent was withdrawn in 83% of patients, with antimetabolites being the most frequent. Steroids were generally not stopped and the dose was even increased in 15% of patients as part of the treatment of COVID-19. Although immunosuppressive drugs were suspended during a median time of 17 days, no rejection episodes neither de novo donor specific antibodies were observed up to 3 months after discharge, and no significant changes occurred in calculated panel reactive antibodies. Acute graft dysfunction was common (55%) and the severity was related to tacrolimus trough levels, which were higher in patients receiving antivirals. At the end of follow-up, all patients recovered baseline kidney function. Conclusion: Our observational study suggests that immunosuppression in KTs hospitalized due to COVID-19 could be safely minimized.